Gingival Curettage for Management of Generalized Chronic Periodontitis : A Case Report - Sulistiawati; Fajar Wijayati, Diska (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Introduction: Periodontitis is a risk factor that contributes to impaired masticatory function and tooth loss. Periodontal disease is caused by bacteria contained in plaque on the surface of the teeth. Plaque is a thin layer of biofilm containing a collection of pathogenic microorganisms. The porous surface due to the presence of calculus allows accumulating plaque. The formation of plaque or biofilm can be prevented mechanically by brushing the teeth and cleaning the interdental teeth using dental floss. Case report: A 50 year old male came to the Rumah Sakit Khusus Gigi dan Mulut Prov. Sumatera Selatan complained that his teeth feel rough and dirty, especially on his lower front teeth. This complaint has been felt for approximately 2 years. Intraoral examination showed reddish gingiva, rounded interdental papillae, unstippling texture, soft consistency on the sextant e of the anterior mandible. bleeding on probing was positive in all regions, probing depth of tooth 31 was 5 mm.Conclusion: During evaluation 1 week and 1 month after curettage the patient had no complaints and there were good gingival changes.